2006
DOI: 10.1177/0022022106288481
|View full text |Cite
|
Sign up to set email alerts
|

Reverence for Mothers in Ecuadorian and Euro-American Culture

Abstract: Two studies examine differences between Ecuadorians and Euro-Americans in levels of reverence for their mothers. Data collected from college students in Ecuador and the United States show that Ecuadorians display higher levels of mother reverence than Euro-Americans. Ecuadorians also score higher on measures of maternal power, similarity of mothers to the cultural ideal of women, and uncertainty avoidance. However, levels of independence are significantly higher in the Euro-American sample than in the Ecuadori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 17 publications
0
9
0
2
Order By: Relevance
“…It is worth noting that the findings in Ecuador differ from those in earlier research comparing independence among Ecuadorians and Euro-Americans. Previous studies by Mealy et al (2006; Mealy et al, 2007) revealed that Euro-Americans reported higher levels of independence than Ecuadorians. The most plausible explanation for this increase is that individualism is increasing in Ecuador, as it is in many other parts of the world (Allen et al, 2007; Hofstede, 1980; Smith & Bond, 1998) due to urbanization, globalization, education, and changes in communication technology.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…It is worth noting that the findings in Ecuador differ from those in earlier research comparing independence among Ecuadorians and Euro-Americans. Previous studies by Mealy et al (2006; Mealy et al, 2007) revealed that Euro-Americans reported higher levels of independence than Ecuadorians. The most plausible explanation for this increase is that individualism is increasing in Ecuador, as it is in many other parts of the world (Allen et al, 2007; Hofstede, 1980; Smith & Bond, 1998) due to urbanization, globalization, education, and changes in communication technology.…”
Section: Discussionmentioning
confidence: 90%
“…The uncertainty avoidance measure was developed by Mealy, Stephan, and Abalakina-Paap (2006). It contained 10 statements with a 6-point Likert-type response format scale.…”
Section: Methodsmentioning
confidence: 99%
“…Women may also be coming from cultures where the mother role is more integral and revered than in North America. For example, research has identified that in the Ecuadorian culture, the role of mother is closely linked to the cultural ideal of woman and is held in higher esteem relative to Euro-American culture (Mealy et al, 2006). Women coming from cultures where the mother role is revered may experience postpartum distress during the post-migration period as a great personal failure.…”
Section: A Period Of Mourning Versus Ppdmentioning
confidence: 99%
“…Vandello et al [35] указывается, что в странах Латинской Америки преобладает «марианизм», согласно которому образцом является Дева Мария; идеальная женщина жертвует собственными интересами ради интересов семьи и реализуется преимущественно в роли жены и матери. У американцев европейского происхождения идеалом женщины является сильная и независимая «суперженщина», которая уделяет внимание не только семье, но и карьере [29]. Отечественными исследователями также изучаются представления об идеальном супруге и распределении семейных ролей у представителей народов, проживающих на территории РФ [6,13].…”
Section: Introductionunclassified